2020
DOI: 10.3390/en13246648
|View full text |Cite
|
Sign up to set email alerts
|

Bubbles in Crude Oil and Commodity Energy Index: New Evidence

Abstract: This paper considers a long dataset of both Brent and West Texas Intermediate (WTI) crude oil prices and the Commodity (fuel) energy index (CEI) to identify possible bubbles. Using the Supremum Augmented Dickey–Fuller (SADF) test, we compare results from WTI and Brent with CEI. We prove that the CEI follows Brent crude oil (they provide similar bubble periods) and that Brent is recognized as a crude oil benchmark. Financial managers should incorporate it into their analysis and forecasts. The findings are stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The literature on bubble formation in commodities and asset markets is often built on Phillips et al's (2013Phillips et al's ( , 2015 theoretical works. Several studies, in addition to identifying multiple bubble episodes, have tried to identify the events leading to the formation of the commodity and asset price bubbles (see Balcilar et al, 2014;Caspi et al, 2014;Floros & Galyfianakis, 2020;Gronwald, 2016;Khan, Su, & Rehman, 2021;Li et al, 2022;Liu & Lee, 2018;Su et al, 2017Su et al, , 2020Umar et al, 2021;Yang et al, 2021). Some of the studies in this area have found that economic policy uncertainty has an asymmetric effect on energy consumption, meaning that adverse changes in uncertainty have a larger impact than positive changes (Sarker et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on bubble formation in commodities and asset markets is often built on Phillips et al's (2013Phillips et al's ( , 2015 theoretical works. Several studies, in addition to identifying multiple bubble episodes, have tried to identify the events leading to the formation of the commodity and asset price bubbles (see Balcilar et al, 2014;Caspi et al, 2014;Floros & Galyfianakis, 2020;Gronwald, 2016;Khan, Su, & Rehman, 2021;Li et al, 2022;Liu & Lee, 2018;Su et al, 2017Su et al, , 2020Umar et al, 2021;Yang et al, 2021). Some of the studies in this area have found that economic policy uncertainty has an asymmetric effect on energy consumption, meaning that adverse changes in uncertainty have a larger impact than positive changes (Sarker et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study joins the literature that employs the SADF and GSADF tests to identify the specific periods of price exuberance. These studies include Su et al (2017), Liu and Lee (2018), Floros and Galyfianakis (2020), Su et al (2020), Umar et al (2021), Khan, Su, Umar, et al (2021), Li et al (2022), andYang et al (2021). In addition, the use of the logit model to determine the impact of uncertainties on price exuberance can be seen as an extension of the work of Wang and Kim (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted to investigate price bubbles in energy markets. Floros and Galyfianakis (2020) employed the Supremum Augmented Dickey-Fuller (SADF) test to detect bubbles in BRENT and WTI crude oil prices, with the former index being the benchmark for the latter. Alternately, Su et al (2017) found multiple explosive bubbles in the WTI crude oil market from 1985 to 2016 using the GSADF test.…”
Section: Price Bubbles In Energy Marketsmentioning
confidence: 99%
“…Other papers in the field (e.g., Maslyuk and Smyth [6]) have focused on various non-renewables energy series, with their analyses relying on a wide variety of techniques. Unit-root/stationarity testing is also being employed to detect potential bubbles in asset prices (e.g., Perifanis [7] and Floros and Galyfianakis [8] have studied the case of crude oil prices).…”
Section: Introductionmentioning
confidence: 99%